ANALISIS KINERJA PEGAWAI PADA KANTOR LURAH LEOK I KECAMATAN BIAU KABUPATEN BUOL - Satria (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2022)
The aim of this research is to find out the description of employee performance at the Leok I Village Head Office, Biau District, Buol Regency. The research method used is a qualitative descriptive research method. The research location is the Leok I Village Head Office, Biau District, Buol Regency. The time for this research is two months, namely August to September 2022. The data collection techniques used are Observation, Interview Guide, Documentation, in the research Qualitative Descriptive Data reduction, Data presentation, Final stage. The results of the research reveal that the performance of employees at the Leok I Biau Village Head office, Buol Regency is good, based on various factors such as work quality, work quality, work quality, work quality, work quality. work, and quality of work. This shows that the performance of employees at the Leok I Village Head is good.